THREE ECONOMIC AUDITS IN THE INTERLUDE BETWEEN TWO WORLD WARS. - Brady, Robert E. (The Accounting Review, 1943)
Reviews three books "Final Report of the Committee on Industry and Trade," "Enqueteausschuss—A usschuss zur Untersuchung der Erzeugungsund A bsatzbedingungen der deutschen Wirtschaft" and "Temporary National Economic Committee on the Concentration of Economic Power in the United States."